Applying YUV Color Mode in Color Image Processing by Using Java Swing - Kamel Shariah, Sawsan (2001)
One of the most exciting new areas In computer technology is the development in color image processing field. Image processing is used to improve the visual quality of an image. Jaguar Java Software is a GUI (Graphical User Interface) software, powerful yet very simple to use, provides the means to filter color images in RGB Color space and YUV Color space, to produce high quality filtered images. YUV Color space model proved to filter images in a smooth way without loosing any data, only enhancing the image structure. Different images were applied, and satisfactory results were obtained of multi-applications objectives. Swing was used as the main programming language, which is part of the Java Foundation Classes (JFC) library. It offers much improved functionality as new components, expanded component features, better event handling.